Guide to industries: policies & procedures - Jain, Rajiv (Delhi, 1988)
The book is a compilation of Government Policies announced from time to time on Industries. Besides, Procedure for Setting Up of Industry, Registration & Licensing of Industry have been explained along with Facilities, Incentives and Concessions offered by the Government to the Enterprise. This will serve as a Guide to the Entrepreneurs engaged in Industrial activities.